(untitled) (CIPEEX, 2023)
The objective of this study was to compare the accuracy of periapical radiography (Rx-P) and cone beam computed tomography (CBCT) in detecting inflammatory root resorption. Fourteen patients referred to the Emergency Service were evaluated (8 female; 57.14% and 6 male; 42.86) aged between 18 to 64 years. The sample consisting of 52 teeth was divided according to their dental group, with 6 being anterior, 23 premolars, and 23 molars. The number of roots analyzed was 88. Regarding the diagnosis, the classifications were as follows: periapical abscess without fistula phase I (n = 1; 1.92%), pulpal necrosis (n = 1; 1.92%), asymptomatic apical periodontitis (n = 36; 69.23%), symptomatic apical periodontitis (n = 14; 26.92%). Regarding the type of infection, 42 (80.77%) teeth presented with primary infection and 10 teeth (19.23%) with secondary infection. High prevalence was observed after the use of tomography. However, there was no statistically significant difference between Rx-P and TCFC. Advances in clinical evaluation have greatly improved diagnostic accuracy. CBCT allows for a greater likelihood of correct management of resorption lesions compared to intraoral radiographs.